Derailed locomotive? Petrobras investments and economic growth in Brazil - Raíssa Fernandes Yabiko; Rosemarie Bröker Bone (International Journal of Production Management and Engineering)
Petrobras is the largest firm in Brazil and one of the largest in the world. Its investment plans are among the biggest in the oil and gas industry, focused in Brazil and on E&P. Petrobras is responsible for a large share of gross capital formation and gross domestic product (GDP) growth in the country. The correlation between its investments and the country investment and GDP growth is above 0.8 and shows the dependency of the economy to Petrobras activity. At the same time, as a state enterprise it has been a tool of macroeconomic policy. In the 2010´s its gasoline and diesel prices were frozen to keep inflation down. The recent crisis in the company, including corruption scandals and oil price slump increased debt levels and reduced its capital expenditures. The sale of assets directive since 2016 is required to reduce its net debt. While a medium to long term survival strategy, the change in Petrobras’ investment profile may decrease the prospects of GDP growth in the Brazilian economy.